Removal of xylene and toluene vapors in classical biofilter and biotrickling filter - De la Cruz, Donato Santiago
Biofiltration is a process that utilizes microrganisms to metabolize and convert pollutants into harmless byproducts such as water and carbon dioxide. This process was employed in the removal of xylene and toluene vapors in air using a bacterial consortium that completely mineralized thesepollutants. Kinetics study conducted as part of this research showed that the bacterial consortium degraded p- and m- xylene and toluene following Monod model and did not degrade o-xylene and benzene. Two methods were used and compared in the determination of degradation kinetics-headspace sampling and optical density measurement. Results showed that there was no significant difference in these two methods as far the determination of kinetic parameters is concerned. The effects of different operating parameters on removal of xylene and toluene vapors were measured in both classical and biotrickling biofilters. The effects of space time, inlet gas concentration and medium addition on the removal of xylene and toluene in classical biofilter and biotrickling filter and of liquid recirculation rate and frequency of medium change on biotrickling filter performance were analyzed. Experimental results showed that the addition of fresh mineral medium in the classical biofilter increased its elimination capacity (EC). While replenishment of recirculating mineral medium in the trickling biofilter increased eleimination of xylene and toluene. Increased recirculation rate in the biotrickling filter increased removal of toluene or xylene until an optimal recirculation rate was reached. The value of the optimal recirculation rate was dependent on the inlet concentration of the substrate, with higher optimal recirculation rate at higher inlet substrate concentrations. Comparison of the performance of the classical and trickling biofilters showed that considering only elimination capacity, the biotrickling filter is better choice. Although the biotrickling filter has a EC, especially at high substrate concentrations, the added cost of medium replenishment was a factor that must be balanced with higher EC in determining which of the two type of filters is the optimal choice.